Thermo-hydraulic design of a gasketed-plate heat exchanger for liquid cow’s milk cooling - Pérez Sánchez, Amaury; Arias Águila, Laura de la Caridad; Jiménez Guerra, Lizthalía (Ingeniería Química y Desarrollo, 2026)
Plate heat exchangers offer greater compactness compared to tubular exchangers. The plate configuration enhances heat exchange by creating an extensive and fully compact area that allows for the efficient heat transfer between two fluids. The present paper aims to design, from the thermo-hydraulic point of view, a gasketed-plate heat exchanger to cool down a stream of hot liquid cow’s milk using chilled water as coolant. Several important parameters were determined such as the total number of plates (3), the heat load (163.79 kW), the required mass flowrate of chilled water (5,638 kg/h), the required surface area (2.21 m2) and the overall heat transfer coefficient calculated (2,194.06 W/m2.K). Likewise, the values of the pressure drops for the water (48,558 Pa) and milk (14,720 Pa) streams are below the maximum permissible values set by the process. The designed plate heat exchanger will cost USD 2,692 and can be successfully implemented in this heat transfer service from the thermo-hydraulic perspective.